The Last Mile to Quality Service Delivery in Jordan - Rabie, Tamer Samah (Washington, DC: World Bank, 2017)
A growing body of research suggests that the quantity and quality of structural inputs of education and healthcare services such as infrastructure, classroom and medical supplies, and even teacher and medical training are largely irrelevant if teachers and healthcare providers do not exert the requisite effort to translate these inputs into effective teaching and medical service. To exert adquate effort, providers must feel they are accountable for the quality of service they provide. Yet a sense of accountability among providers does not necessarily occur naturally, often requiring mechanisms to monitor and incentivize provider effort. The literature on improving provider accountability has under-emphasized the role of monitoring practices by school principals and chief medical officers.